Exploring Slave Trade in Asia : First Steps towards an International Database - Konings, Pascal; Hids, Maartje; Miske, Sam J.; van Rossum, Matthias; Tosun, Merve; de Korte, Hannah (TSEG - The Low Countries Journal of Social and Economic History, 2023)
Since its conception in 2016, the Exploring Slave Trade in Asia (ESTA) project has been working towards solidifying research on the slave trade in the Indian Ocean region and Maritime Asia world by means of a collaborative database. This article briefly discusses ESTA’s roots and goals, showcasing the first results that its database yielded. We discuss and evaluate the database’s structure and content up until this point, as well as its ramifications, aspirations, and challenges. Based on the first observations, this article further signifies the value of the ESTA database for comparative slave trade research, taking its first steps towards a reconstruction of the Indian Ocean and Maritime Asia slave trade by connecting global long-distance slave trade with local systems of slavery and forced labour.